Chromatin topology is coupled to Polycomb group protein subnuclear organization - Ajazul H. Wani (Nature Portfolio, 2016)
Polycomb Group (PcG) proteins regulate gene expression and genome architecture. Using super-resolution microscopy and molecular simulations, Waniet al. describe the organization of PcG proteins into hundreds of nano-scale protein clusters and suggest these clusters shape genome architecture.